“TAKIPSILIM”: A Fantasy-Themed 2D Turn-Based RPG Developed Using Unity Engine - Capundan, Paolo Angelo P.; Evangelista, Mark Steven P.; Libutan, John Andrei K.; Bariso, Kurtz Warren G.; Bunag, Ferdinand (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – Role-Playing Games (RPG) are an iconic genre for both tabletop and video game mediums that remains relevant even to this day. With the popularity of video games, it was inevitable that RPGs would also appear in this medium. In this study, the researchers aim to develop a Fantasy-Themed 2D Turn-Based RPG developed using the Unity Engine that will enrich and educate people about Filipino mythological creatures, folklore, cultures, and traditions. Method - The agile methodology was used in game development, which provided the developer with the ability to deliver faster value, better output quality, and the flexibility to make the necessary game adjustments. The study was broken down into smaller modules and consistent idea collaboration was done together with the stakeholders. The development of TakipSilim was created using the C#-based Unity Engine Language, built on the Unity Engine. The game storyboard was used to familiarize the developers with the game’s story progression and challenges. Results - For the findings, the system’s evaluation was conducted on twenty (20) gamers in terms of gameplay, efficiency, reliability, usability, compatibility, maintainability, and difficulty and was based on the ISO/IEC 25010:2011 standard. The game was also evaluated by IT experts using different criteria. As a result, a very satisfactory rating of 4.7 was given to readability, ease of program maintenance, low hardware resource consumption, and low complexity. The only Source Code Adaptation received a higher rating of 4.8, which was also very satisfactory. Conclusion - The study reveals that the game developed was able to provide its users with the gaming experience to promote, enlighten, and educate people about the local culture through folktales, mythological creatures, and superstitions. The game has functions and features that have a unique storyline written by the proponents and proves that there is quite a demand for Filipino-themed games, though niche, in the market today. Recommendations – The proponents recommend and encourage future researchers to take the initiative to expand the horizons in game development revolving around Filipino culture due to the demand for the game revolving around the mythos.  Research Implications - The  study has shown that the agile software methodology provided the developer with the ability to deliver faster value and better output quality. Also, the system evaluation was implemented based on the basic ISO standards which results in a very satisfactory rate. Lastly, creating RPG games from the ground is very challenging for amateurs, but they it able to grow and hone their skills as researchers and game developers.